(untitled) (Quinto Sol, 2013)
From a historical perspective, the problem of the intensity of livestock use of the land in the Pampean meadows has been central in any analysis of the agrarian economy of the 19th century. However, up to now, historians have used very general occupation or livestock receptivity rates to use them in all periods and in all sub-regions of the Pampean prairies. Based on the historiographic progress of recent years, it is necessary to make a much more refined analysis and this article is framed in that direction.